Analyzing the Impact Of Traditional Market Relocation In Surrounding Traders And Communities (Case Study Of Demak Mranggen Markets) - Soelistiyono, Anitiyo; Adrianto, Andhy Tri; Kurniawati, Emaya (Economics and Business Solutions Journal, 2018)
Traditional markets are markets that are built and managed by local governments. Relocation of a transfer of supporting facilities and infrastructure activities from one place to another in order to enhance the security, comfort and legality factors.Mranggen traditional market is one of the markets located in the village of Mranggen which is increasingly experiencing an increasing number of traders. For this reason, the Demak Regency Government decided to relocate the market, one of them is the traditional Mranggen market, the government's purpose of relocating Mranggen's traditional market to tidy up the former market which had not been neatly arranged. Mranggen's market relocation had an impact or pros and cons for traders and the surrounding community. The problem in this study is the impact of market relocation of Mranggen's traditional market relocation to traders in the surrounding community. The aim of the study was to determine the impact of Mranggen's traditional market relocation to both traders and the surrounding community with market relocation.The research design used in this study is a holistic single case study. This study uses a qualitative approach. The types and sources of data used in this study are primary data and secondary data. The object of the research was conducted at the temporary shelter of Mranggen village. Informants are traders and communities around the shelter. Data collection techniques with triangulation.As for eclectic data analysis techniques. In this study, the validity of the research data was tested by credibility, transferability, dependability test, and confirmability test.The results of our research on the impact of relocation on product quantity is the reduction in product quantity ranging from 30% to 50%. With regard to operating hours the impact of this relocation is a reduction in operating hours of only 6-8 hours per day. For the position of the stall The inconvenience of the stall position, the stinging smell of garbage, and when the rainy season often floods and lacks security. In terms of ease of reaching the location, the traders complained about the location of the remote relocation and the narrow road to relocation which affected the consumers' desire to buy. With this relocation, sales turnover has decreased from 75,000-250,000/day.